Clinicopathologic Features Of Langerhans Cell Histiocytosis At Hasan Sadikin Hospital In 2010-2020 - P, Lestari (Jurnal EduHealth, 2024)
Langerhans Cell Histiocytosis (LCH) is a rare neoplasm of myeloid origin, characterized by the proliferation of Langerhans cells expressing CD1a and CD207. While primarily affecting children, LCH can also occur in adults, though the incidence is extremely low. The disease manifests in various clinical forms, often complicating diagnosis and management. This study aims to describe the clinicopathological aspects of LCH cases treated at Hasan Sadikin Hospital (RSHS) Bandung over a ten-year period, from 2010 to 2020. Clinicopathological data of patients diagnosed with LCH at the Anatomical Pathology Department of Hasan Sadikin Hospital from 2010 to 2020 were retrospectively reviewed. Data collected included patient age, gender, anatomical location of the disease, and sampling methods used for diagnosis. Diagnosis of LCH was confirmed through morphological assessment of histopathologic specimens and fine needle aspiration biopsy (FNAB) smears. LCH remains a rare entity characterized by the abnormal proliferation of Langerhans cells, predominantly affecting children and most frequently involving the head region. Typical cytologic and histopathologic features are usually present, aiding in the diagnosis. However, variability in presentation underscores the importance of integrating clinical, radiologic, and immunohistochemical data for accurate diagnosis. Further research is warranted to explore long-term outcomes and optimal management strategies, particularly in regions with limited case data.